The Inter-Generational Transmission of Indigenous Knowledge By Nenets Women: Viewed in the context of the state educational system of Russia - Ravna, Zoia Vylka (Arctic Anthropology, 2020)
Nenets reindeer herders of the Russian arctic are described by researchers as the most successful, in terms of the number of their reindeer and the number of people involved in this unique way of life. However, the continuation of this unique form of nomadic culture is at immediate risk. There is a problem, the recruitment and training of future generations of nomadic Nenets reindeer herders, in order to replace an ageing population, is being undermined by the current educational policies of the Russian state. Due to the state’s compulsory educational system for the nomadic Nenets population, based on boarding schools, Nenets children are removed from their nomadic communities for more than 8 months a year. Until now, the nomadic Nenets people have historically created their own unique family-based system for the inter-generational transmission of traditional knowledge and skills, in order to educate their children to survive and live on the tundra. This system, including specific ways to bring up their children to become Tenevana – “knowledgeable” and “to have a great mind based on experience”, is nowadays disrupted by the requirements of a compulsory state education system. Based on ethnographic and pedagogical research, I found that there are significant differences between the two studied groups of nomadic Nenets communities living in arctic Russia. Firstly, in the west, due to the displacement of nomadic women to settlements, there are almost no mother tongue speakers in their state boarding schools. In contrast, the Siberian Nenets children possess a relatively better knowledge of language and necessary skills needed for a life of nomadic reindeer herding on the tundra. Despite these differences, the majority of adolescents from both areas, particularly females, are choosing a settled way of life after graduating from school. My research has indicated that the increasing loss of ageing nomadic Nenets women, who will not be replaced by younger generations of nomadic Nenets women, will end the traditional ...